1994
DOI: 10.1021/np50109a009
|View full text |Cite
|
Sign up to set email alerts
|

Alectosarmentin, a New Antimicrobial Dibenzofuranoid Lactol from the Lichen, Alectoria sarmentosa

Abstract: From the alcoholic extract of the lichen Alectoria sarmentosa, four compounds showing antimicrobial activity were isolated. Of these, (-)-usnic acid and physodic acid are well known lichen products, 8'-O-ethyl-beta-alectoronic acid [2] is believed to be an artifact formed during isolation and fractionation, and alectosarmentin [1] is a new natural product whose structure was shown, by spectroscopy and chemical transformations, to be that of a dibenzofuranoid lactol. The antimicrobial activity of these substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Knowledge of the biological activity of physodic acid and its derivatives is limited. The antimicrobial activity of physodic acid, 3-hydroxyphysodic acid and extracts from H. physodes (Gollapudi et al 1994;T€ urk et al 2003Yilmaz et al 2005;Ranković et al 2007), as well as the antimutagenic activity of physodic and physodalic acids (Shibamoto & Wei 1984;Osawa et al 1991), has been reported. Studies also demonstrated that physodic (Neamati et al 1997;M€ uller 2001) and hydroxyphysodic acids inhibited different enzymes (Proksa et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the biological activity of physodic acid and its derivatives is limited. The antimicrobial activity of physodic acid, 3-hydroxyphysodic acid and extracts from H. physodes (Gollapudi et al 1994;T€ urk et al 2003Yilmaz et al 2005;Ranković et al 2007), as well as the antimutagenic activity of physodic and physodalic acids (Shibamoto & Wei 1984;Osawa et al 1991), has been reported. Studies also demonstrated that physodic (Neamati et al 1997;M€ uller 2001) and hydroxyphysodic acids inhibited different enzymes (Proksa et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The five secondary metabolites that were higher in the thallus than the apothecia may play other roles to protect the photobiont. Arctoparmelia centrifuga produced high thalline quantities of alectoronic acid, which is thought to have some antimicrobial capabilities (Gollapudi et al 1994). Higher quantities of usnic acid in the thallus would be expected if protection of the photobiont from excess UV light is a main function (Armaleo et al 2008;McEvoy et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As certain phenol compounds produced by lichens strongly absorb UVB light, these agents are used as photoprotectors (Fernandez et al 1996), and their antioxidant capacity (Hidalgo et al 1994) warrants their use as preservatives in cosmetic creams. Several lichen extracts have been used for various remedies in folk medicine, and screening tests with lichens have shown the frequent occurrence of metabolites with antibiotic, antimycobacterial, antiviral, antitumor, analgesic and antipyretic properties (Vartia 1973;Crittenden & Porter 1991;Gollapudi et al 1994;Huneck 1999;Müller 2001;). Because of marked antimicrobial activity of secondary metabolites, lichens, macrofungi, and vascular plants attract great attention 54 B. Ranković et al…”
Section: Introductionmentioning
confidence: 99%